Leadership Practices among Private Higher Education Institutions: Basis for Transformational Leadership Model - Jinky Navia (Philippine Association of Institutions for Research, Inc., 2022)
Leadership is the foundation and basis of an organization's success. Its context has been melded in Private Higher Education Institutions by the shifts in technological modes of teaching and learning and its response to the demand of the new generation and competition. The purpose of this research is to identify leadership practices and their effectiveness that will help private higher education institutions achieve institutional goals and vision, manage their operations, maintain good relationships, and lead with a high-quality education. The study used a quantitative research design to determine and assess the effectiveness of leadership practices among private education institutions in the 2nd district of Albay, likewise using descriptive statistics to interpret the study findings. The analyzed data revealed that the respondents 'agree' that their institutional leaders have demonstrated their management skills in terms of academic leadership (3.43), human resources (3.29), financial resources (3. 15), and facilities and equipment (3.09); thus, their leadership skills along intrapersonal skills (3.34), interpersonal skills (3.3), and innovation skills (3.18). However, there are problems encountered by the respondents along with the leadership skills of their leaders. Therefore, developing a transformational model is necessary to address further development and ensure their long-term success and sustainability.